Biotransformation in the zebrafish embryo –temporal gene transcription changes of cytochrome P450 enzymes and internal exposure dynamics of the AhR binding xenobiotic benz[a]anthracene. (November 2017) - Kühnert, Agnes; Vogs, Carolina; Seiwert, Bettina; Aulhorn, Silke; Altenburger, Rolf; Hollert, Henner; Küster, Eberhard; Busch, Wibke
Abstract: Not much is known about the biotransformation capability of zebrafish ( Danio rerio ) embryos. For understanding possible toxicity differences to adult fish, it might be crucial to understand the biotransformation of chemicals in zebrafish embryos i.e. as part of toxicokinetics. The biotransformation capabilities were analysed for two different stages of zebrafish embryos in conjunction with the internal concentrations of a xenobiotic. Zebrafish embryos of the late cleavage/early blastula period (2–26 hpf) and the early pharyngula period (26–50 hpf) were exposed for 24 h to the AhR binding compound benz[ a ]anthracene (BaA). Time dependent changes in cyp transcription ( cyp1a, cyp1b1, cyp1c1 and cyp1c2 ) as well as concentration & time-dependent courses of BaA in the fish embryo and the exposure medium were analysed. Additionally, the CYP mediated formation of biotransformation products was investigated. We found correlations between transcriptional responses and the internal concentration for both exposure types. These correlations were depending on the start of the exposure i.e. the age of the exposed embryo. While no significant induction of the examined gene transcripts was observed in the first 12 h of exposure beginning in the blastula period a correlation was apparent when exposure started later i.e. in the pharyngula period. A significant induction of cyp1a was detected already after 1.5 h of BaA exposure. Gene transcripts for cyp1b1, cyp1c1 and cyp1c2 showed expressions distinctly different from cyp1a and were, in general, less inducible by BaA in both exposure windows. The toxicokinetic analysis showed that the biotransformation capability was fivefold higher in the older fish embryos. Biotransformation products of phase I reactions were found between 32 hpf and 50 hpf and were tentatively identified as benz[ a ]anthracene-phenol and benz[ a ]anthracene-dihydrodiol-epoxide. In conclusion, not only duration but also onset of exposure in relation to the developmental stage of zebrafish embryos is important in the analysis and interpretation of effects due to different biotransformation capabilities. Graphical abstract: Highlights: Starting time of exposure is important for induction of biotransformation. Biotransformation capabilities may differ between embryonic stages of zebrafish. Significant induction of cyp1a was already detected after 1.5 h of BaA exposure. Abstract : Not only duration but also onset of exposure in relation to the developmental stage of zebrafish embryos is important for toxicity assessment.